A twentieth-century prophet : Oscár Jászi, 1875-1957 - Litván, György (Central European University Press, 2006)
"This volume represents the first ever extensive biography of Oscar Jaszi, historian, political theorist and sociologist, who dedicated his tremendous intellect to modern democracy in Hungary. A man exiled from his homeland, Jaszi's moral courage stood strong against the political tyranny and totalitarianism of the interwar period that nearly destroyed Hungary's political and social foundations. From his early years as co-founder and editor of the influential Hungarian periodical "Twentieth Century" to his later life as professor at Oberlin College in Ohio, he worked tirelessly for the values of liberalism and humanism, fused with the notion that "a new moral, social, and economic synthesis is needed."" "In this work, the details of Jaszi's life reveal the poignant tragedies and accomplishments that befit a man who refused to compromise his intellectual and moral beliefs, even as he witnessed the dismemberment of his country, two world wars, and the rise of radical ideologies. What was at stake was no less than the very spirit of democracy and intellectual freedom. In this sense, the life of Oscar Jaszi represents one of the great triumphs of reason over violence, regardless of the defeat of his vision for a 'Danubian Federation, ' and his subsequent exile. His vow to not be buried in an undemocratic Hungary was kept, and as his country emerged from the ruins of the Soviet block, his remains were transferred to Budapest in 1991, a symbol of his lasting philosophy and the spirit of his will."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved